Fueling financial stability: The financial impact of U.S. renewable fuel standard - Karel Janda; Jan Sila; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Oil price shocks, which materialize in petrol prices, put severe inflationary pressures on countries that rely largely on fossil fuels, causing financial instability. The Renewable Fuel Standard (RFS) program, implemented in the USA in 2005, sanctions blending corn-based ethanol with fuel and can offset oil price shocks. RFS is a technological innovation that protects against inflationary pressures while being ecologically beneficial. We examine how global oil price changes affect US petrol costs and the resulting savings for US families by assessing the program's effectiveness. Our findings show that blending ethanol into petrol serves as a buffer against global oil price shocks, delivering an average 0.185 per gallon savings from 2019 to 2022. This translates to 22.8 billion in annual savings for American consumers. As the global debate shifts towards sustainable energy and climate change mitigation, our findings highlight the practical benefits of diversifying energy sources, which promote both environmental sustainability and economic stability in the face of volatile commodity price shocks.
Keywords: C22; E63; Q42; Q41; 330; Financial stability; Commodities; Energy markets; Technological Innovation; Ethanol; U.S.A